The Effect of Reproductive Health Education About Menstrual Disorders on Adolescents at The Al-Madinah Integrated Islamic Boarding School, Malati Jonggol Village in 2024 - Juwita, Sinta Dwi; Aprianti, Nurul Azmi; Hidayah, Nur Rahmah (Ridwan Institute, 2025)
Menstruation usually occurs for 3-7 days. The time period from the first day of menstruation to the first day of menstruation the following month is called the menstrual cycle. The menstrual cycle pattern is said to be normal if it occurs not <21 days and not >35 days. Menstrual cycle disorders that many women experience are cycles that last >35 days (oligomenorrhea), short menstrual cycles <21 days (polymenorrhea), and even not experiencing menstruation for 3 months in a row (amenorrhea). Objective: The aim of this research is to determine the influence of polymenorrhea education in adolescents on adolescent knowledge at the Terpadi Al-Madinah Jonggol Islamic Boarding School in 2024. Research Method: This research is quantitative with a quasi-experimental type of research through pretest and post-test activities. Results: The results of the study showed that there was an increase in knowledge after being given reproductive health education about polymenorrhea in adolescents. Conclusion: There is an effect of increasing knowledge after providing education to adolescents on reproductive health.